MEMBANGUN PARADIGMA BARU PENGELOLAAN ZAKAT KOTA PALU DALAM PERSPEKTIF UU NOMOR 23 TAHUN 2011 - Ahmadan B Lamuri (Fakultas Syariah (Syari'ah Faculty ), 2016)
Abstract Zakat is a potential instrument of Muslim common economy interest that needs managing though a particular institution. The presence of such institution shifts a traditional paradigm of zakat management: zakat was identical to ustadz and tended to be consumptive. And often, it was managed by a special committee. The descriptive analysis of data gained from primary and secondary source on the effort of BAZNAZ of Palu local government shows that BAZNAZ was founded as a commitment to implement acts of zakat in Indonesia. Further, it changed the paradigm of zakat management that focused more on ritual instead of social purpose. Whereas, zakat was aimed at reducing the number of poverty and other problems related to social welfare. Therefore, the presence of BAZNAS in Palu could change the paradigm of its citizens on term of muzakki, mustahik, and amil. Besides, it could overcome economic and social problems faced by Muslim in Palu. Keywords: Paradigm, management of zakat, BAZNAS.